An Epidemiological Study of Suffocation Deaths In Twin Cities of South India - Maddileti, Gandla Bala; Mohanty, Sujan Kumar; Kumar, Virendra; Reddy, K Bhaskar; Bhuvan, V; Yamini , K (Journal of Indian Academy of Forensic Medicine, 2015)
In spite of advancement in medical facilities, the end of life is inevitable. Suffocation deaths have  increased over the years and are becoming a large group in medico legal autopsies. In such deaths, a  detailed and meticulous autopsy plays a major role to solve the case, while the scene visit and collection  of samples have their own significance. To analyse the recent trends such as manner, methods, motive  etc., in suffocation deaths, a prospective study was conducted for two years period. 34 suffocation deaths  were studied, which comprised 0.18% of all Forensic autopsies; 38.23% of the cases were aged between  21-30 years. Males constituted 67.63% of all the cases. The most frequent method of suffocation death  was smothering (35.29%) followed by environmental and traumatic asphyxia (20.58%), choking (17.64%)  and positional asphyxia (5.88%). The most common manner of suffocation was found to be accidental  (67.64%). But in homicidal cases (29%), the common motive was domestic disputes. Only 30% of  suffocation victims were found positive for blood alcohol.
Keywords: Autopsy; Domestic Violence; Suffocation; Smothering; Traumatic Asphyxia